Do tanger e do cantar no mosteiro cisterciense de S. Bento de Cástris no período moderno - Conde, Antónia Fialho (2020)
Abstract: The sixteenth century was marked by intense reforms in the Catholic Church which, after the Ecumenical Council of Trent (1545-1563), were also reflected in women's religious communities. The daily life of these communities was marked, also at the level of musical practice (instrumental and vocal), by the intervention of local prelates or religious from the male monasteries. Despite the attempt of the Council to standardize religious life also in the field of music, the communities end up demonstrating identity practices that can be better understood from their documentary collection, as is the case of the Cistercian monastery of S. Bento de Cástris. Resumo: O século XVI ficou marcado por intensas reformas na Igreja Católica, que, após o Concílio Ecuménico de Trento (1545-1563) se refletiram também nas comunidades religiosas femininas. A vida quotidiana destas comunidades ficou marcada, também ao nível da prática musical (instrumental e vocal), pela intervenção de prelados locais ou de religiosos oriundos dos cenóbios masculinos. Apesar da tentativa de uniformização da vida religiosa pelo Concílio também no domínio da música, as comunidades acabam por demonstrar práticas identitárias que podem ser melhor entendidas a partir do seu acervo documental, como é o caso particular do mosteiro cisterciense de S. Bento de Cástris.